Analyzing Language Politeness of Maxim of Courage Produced by Students in the Mobile Legends Game - Murni, Maria Evriana Priska; Simanjuntak, Nensy Megawati; Dedi Setyawan (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Online games, particularly Mobile Legends, have become highly popular among students, especially college students. While engaging and entertaining, this attraction can lead students to neglect important aspects of their behavior, including their language use. This research focuses on the impact of online gaming on language politeness among Unitomo students living in Pumpugan 3, Surabaya. Specifically, the study aimed to examine the influence of frequent online gaming on the level of language politeness among these students, with a qualitative research design conducted in April 2024. The study focused on five Unitomo students, consisting of three female and two male participants, who were active Mobile Legends players. Data collection methods included interviews and observations, providing insights into the students' everyday language use. The results revealed that the environment, particularly time spent playing online games, significantly affected their language politeness. The students often adopted words and phrases from the online gaming environment into their daily conversations, including vulgar language such as